De Kooning : a retrospective - Elderfield, John.; De Kooning, Willem, 1904-1997.; Mahony, Lauren; Field, Jennifer; Huisinga, Delphine; Coddington, James; Lake, Susan; Frankel, David, 1954-; Museum of Modern Art (New York, N.Y.) (New York : Museum of Modern Art : Distributed in the U.S. by D.A.P./Distributed Art Publishers, Inc., 2011)
Overview: Published in conjunction with the first large-scale, multi-medium, posthumous retrospective of Willem de Kooning's career, this publication offers an unparalleled opportunity to appreciate the development of the artist's work as it unfolded over nearly seven decades, beginning with his early academic works, made in Holland before he moved to the United States in 1926, and concluding with his final, sparely abstract paintings of the late 1980s. The volume presents approximately 200 paintings, sculptures, drawings and prints, covering the full diversity of de Kooning's art and placing his many masterpieces in the context of a complex and fascinating pictorial practice. An introductory essay by John Elderfield, MoMA's Chief Curator Emeritus of Painting and Sculpture, provides an in-depth exploration of de Kooning's development, context and sources, theory of art and working methods. Sections devoted to particular areas of the artist's oeuvre provide an illustrated chronology of the period and a brief introduction, as well as detailed entries on groups of works. With lavish, full-color documentation, this landmark publication is the most complete account of de Kooning's artistic career to date.
Foreword --Preface --Space to paint / John Elderfield --Chapter 1: Early Work / Lauren Mahony: --Chronology: 1904-1937 / Delphine Huisinga --Dutch still lifes --Early New York still lifes --WPA and related works --Chapter 2: Men, Women, And Interiors / Jennifer Field: --Chronology: 1938-1945 / Delphine Huisinga --Portrait drawings --Paintings of men --First woman series --Methods and materials: Queen of Hearts / Susan F Lake --Abstractions --Chapter 3: Pink Angels To Black-And-Whites / John Elderfield: --Chronology: 1946-1948 / Delphine Huisinga --Pink Lady, Pink Angels --Around Judgment Day --Methods and materials: Judgment Day / Susan F Lake --Men and women, and women without men --Grotesque, ludicrous and fearful --De Koonig's first solo exhibition --Methods and materials: Painting / Jim Coddington --Outright 'abstract' painter --Chapter 4: Around Excavation / Lauren Mahony: --Chronology: 1948-1950 / Delphine Huisinga --At Black Mountain --Second woman series --Methods and materials: Woman / Susan F Lake --Enormous deed --Methods and materials: Excavation / Jim Coddington --Works on paper --Chapter 5: Woman To Landscape / John Elderfield: --Chronology: 1950-1956 / Delphine Huisinga --Beginnings of woman I --Woman I continued; Woman II and Woman III --Methods of materials: Woman II / Jim Coddington --Theme of the woman --Woman and landscape --Methods and materials: Easter Monday / Susan F Lake --Chapter 6: Full Arm Sweep / Jennifer Field: --Chronology: 1957-1963 / Delphine Huisinga --Transition --Abstract parkway landscapes --Black and white --Abstract pastoral landscapes --Methods and materials: Door to the river / Susan F Lake --Chapter 7: Starting Over In Springs / Lauren Mahony: --Chronology: 1964-1969 / Delphine Huisinga --Figures in water --Methods and materials: Woman, Sag Harbor / Susan F Lake --Works on paper --Figures in landscape --Chapter 8: New Directions / Jennifer Field: --Chronology: 1969-1978 / Delphine Huisinga --Hollander workshop --Sculpture --Kind of transfiguration --Methods and materials: Whose name was writ in water / Jim Coddington --Chapter 9: Late Paintings / John Elderfield: --Chronology: 1979-1997 / Delphine Huisinga --Ribbons --White paintings --Garden paintings --Methods and materials: Rider (Untitled VII) / Jim Coddington --List of references --Index of illustrations --Acknowledgments --Trustees of The Museum of Modern Art.
"Published in conjunction with the exhibition de Kooning: a retrospective, at the Museum of Modern Art, New York (September 18, 2011-January 9, 2012), organized by John Elderfield, Chief Curator Emeritus of Painting and Sculpture."
Includes bibliographical references and index.
Keywords: De Kooning, Willem, -- 1904-1997 -- Exhibitions; Abstract expressionism -- Exhibitions